Thermal transport in nano-porous insulation of aerogel: Factors, models and outlook. (October 2015) - Tang, G.H.; Bi, C.; Zhao, Y.; Tao, W.Q.
Abstract: Thermal transport in nano-porous insulation material of aerogel has recently attracted increasing attention due to its extreme low thermal conductivity and the broad applications from energy conservation to safety protection. This work presents a comprehensive overview for thermal transport in nano-porous insulation materials. Factors on thermal insulation from both physical fundamentals and engineering applications are identified, and various prediction approaches including theoretical models and numerical methods for the energy carriers and overall thermal conductivity are discussed as well. In addition, directions for the future studies are looked into and several issues in thermal transport in nano-porous insulation are highlighted. Highlights: An overview is presented for thermal transport in nano-porous insulation material of aerogel. Factors on thermal insulation in nano-porous insulation material of aerogel are identified. Theoretical models and numerical methods for thermal conductivity are compared. Directions for the future investigations are looked into.